Learning strategies for students with disabilities in basic education classrooms in the peruvian Amazon - Juarez Diaz, Juan Rafael (2020)
In the process of educational inclusion, various ways have been tried to take advantage of the conditions in which basic education is developed, allowing the student with disabilities to learn with quality. Therefore, the purpose is to describe the design of strategies in inclusive education to improve the learning process in regular classrooms in the Peruvian Amazon. It is the product of a non-experimental descriptive study, with a sample of 183 teachers. It was found that the teachers of the regular institutions consider the use of basic techniques for the social development of the included child deficient, little use of multiple intelligences and active participation. For their part, teachers in inclusive classrooms indicate that techniques for resolving conflicts and decision-making techniques have not been incorporated. The teachers of the special center consider that importance has not been placed on the management and values ​​of inclusive teachers in the educational process, such as planning, identifying new opportunities to achieve heterogeneous groupings, social development and problem solving and the use of instruments such as the individual orientation plan and the psycho-pedagogical evaluation. Given this, methodological strategies were designed based on the theory of complexity and multiple intelligences that demonstrate their effectiveness, both in their theoretical conception and in practice, demonstrating effectiveness in the achievement of learning by included students.